Review of offshore pipeline span creation mechanism - Shittu, Abdulhakim Adeoye; Kara, F. (Euro Asia : Research and Development Association, 2018)
The various span creation mechanisms have been studied in great detail and this work has presented the state of the art in the area of offshore pipeline span creation mechanism analysis. The different span creation mechanisms of a pipeline during operation include residual uplifts, scouring, sandwaves, underwater landslides, strudel scour, etc. With this information a software can be formulated which can incorporate the different characteristics of elements of span creation.